The potency of horizontal and vertical expansion on food output growth in Sudan: A causality analysis, 1962-2000 - Ameer Mahran, Hatim (Gezira Journal of Agricultural Science; Vol 1 No 2 (2003), 2021)
Against the background of the persistent low productivity and yield in Sudanese agriculture, this paper assesses the performance of various medium-tem plans and programs encapsulated in the national development strategies between 1962 and 2000 vis-à-vis the declared objective of achieving national food security through horizontal and vertical expansion in food production. For this purpose, Hsiao (1979,1981) procedure is used, which combines Granger (1969) causality test procedure and Akaike (1969) final prediction error criterion, to test for causality between growth in output on one hand and growth in area (horizontal expansion) and growth in yield (vertical expansion) on the other hand for three major food crops in Sudan, namely, sorghum, wheat and millet. The results reveal that, in the case of sorghum, it is growth in yield (and not expansion in area) which causes growth in output, while in the case of wheat, neither growth in yield nor expansion in area cause growth in output. The best results are obtained for millet, a crop grown mainly in the traditional sector, where a two-way causality is found between output growth on one hand and growth in yield and expansion in area on the other hand. These results provide the important policy lesson that development strategies should focus more on vertical expansion. Agricultural production and productivity could be increased through the allocation of more investment resources to the sector, not only for the promotion of human capital via the improvement of education, health, and extension services as well as management skills, but also for the provision of adequate infrastructure such as roads, irrigation, research, and markets. It is also argued that such a strategy of vertical expansion is not only viable from an economic point of view since it considerably reduces production cost and improves profitability and international competitiveness, but is also sound in so far as the sustainability of the resources and the environment is concerned.